iMAJALAH / Nur Athika Balqis Mohd Afendi … [et al.] - Mohd Afendi, Nur Athika Balqis; Abd Halim, Nur Hamani Maisara; Rosli, Amrina Khadeja; Ismail, Nur Farah Asyikin; Abd Rahim, Anita (Faculty of Computer and Mathematical Sciences, 2021)
i - majalah is the latest school inovation. It is combined with conventional magazine and e - majalah, which is corresponds to the 21st century where everything is at your fingertips, i - majalah is a cooperation between ict unit and school PSS unit. Either students or others can browse i - majalah easily because it is available on the school website, i - majalah is also available in the form of an apps and will be updated once a year by ICT team on our school website . For students whom do not have telephone , our school lobby provides computers for students to browse i - majalah or they can browse them in the school computer lab . It can save costs because it does not use software and save the environment. The difference in i - majalah compared to conventional magazine is that it has TV PSS Semarak which is our school youtube channel. In conclusion, i - majalah is very useful not only to students and teachers but also to others as well, because it can be used anytime and anywhere